Midwifery education in Canada. (February 2016) - Butler, Michelle M.; Hutton, Eileen K.; McNiven, Patricia S.
Abstract: Objective: This article is part of a special series on midwifery education and describes the approach to midwifery education in Canada Design: We begin with an overview of the model of midwifery practice introduced in Canada in the 1990s. We describe the model of midwifery education developed and report how it is implemented, with particular attention to the two longest established programs. Setting: Midwifery education programs in Ontario and British Columbia. Findings: Midwifery education programs in Canada are offered at the undergraduate baccalaureate level at universities and are typically four years in length. Programs are competence-based and follow a spiral curriculum. The first semesters focus on on core sciences, social sciences and introduction to midwifery concepts. Students spend fifty percent of the program in clinical practices with community-based midwives. Innovative education models enable students to be placed in distant placements and help to align theoretical and practice components. Clinically active faculty adds to the credibility of teaching but bring its own challenges for midwifery educators. Conclusions: The Canadian model of midwifery education has been very effective with low attrition rates and high demand for the number of places available. Further program expansion is warranted but is contingent on the growth of clinical placements.